Hydroxygenkwanin Suppresses Non-Small Cell Lung Cancer Progression by Enhancing EGFR Degradation - Leu, Yann-Lii (Molecules, 2020)
Epidermal growth factor receptor (EGFR) is frequently overexpressed and mutated in non-small cell lung cancer (NSCLC), which is the major type of lung cancer. The EGFR tyrosine kinase inhibitors (TKIs) are the approved treatment for patients harboring activating mutations in the EGFR kinase. However, most of the patients treated with EGFR-TKIs developed resistance. Therefore, the development of compounds exhibiting unique antitumor activities might help to improve the management of NSCLC patients. The total flavonoids from Daphne genkwa Sieb. et Zucc. have been shown to contain antitumor activity. Here, we have isolated a novel flavonoid hydroxygenkwanin (HGK) that displays selective cytotoxic effects on all of the NSCLC cells tested. In this study, we employed NSCLC cells harboring EGFR mutations and xenograft mouse model to examine the antitumor activity of HGK on TKI-resistant NSCLC cells. The results showed that HGK suppressed cancer cell viability both in vitro and in vivo. Whole-transcriptome analysis suggests that EGFR is a potential upstream regulator that is involved in the gene expression changes affected by HGK. In support of this analysis, we presented evidence that HGK reduced the level of EGFR and inhibited several EGFR-downstream signalings. These results suggest that the antitumor activity of HGK against TKI-resistant NSCLC cells acts by enhancing the degradation of EGFR.